Atypical post kala azar dermal leishmaniasis with ''Muzzle area'' swelling - Sandeep Arora; Arvinder Singh Bal; Sukriti Baveja; Aradhana Sood; Khushi Ram Rathi; Pradeep Patil (Wolters Kluwer Medknow Publications, 2015)
A 50-year-old male presented with recurrent swelling of the muzzle area of the face with history of low-grade intermittent fever of 3 year duration managed variously with antibiotics, systemic steroids, and antituberculous therapy. Skin biopsy revealed a granulomatous infiltration negative for acid-fast bacilli and leishmania donovan bodies. Immunochromatography test for rK 39 antigen and polymerase chain reaction for leishmania was positive. He was diagnosed as a case of post kala azar dermal leishmaniasis, managed with injection sodium stibogluconate and followed-up thereafter.